Компьютерно-аналитическая диагностика удельной поверхности порошков сверхтвердых материалов - Новиков, Н.В.; Петасюк, Г.А.; Богатырева, Г.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
New method of determination of outer specific surface of superhard material powders has
been presented. The method is based on 3D-simulation methodology with applying of affinity space
mapping mathematics. The results of this method approbation on grind and micron powders of
DSTU 3292-95 standard have been presented.